Efektivitas Penggunaan Fly Ash Batubara sebagai Koagulan dan Adsorben dalam Menurunkan Chemical Oxygen Demand (COD) dan Total Suspendedd Solid (TSS) Limbah Cair Industri Pulp and Paper - Rahman, Aulia Nauli; Julius, Julius; Viareco, Hariestya (Jurnal Pelita Teknologi, 2022)
The content of Al and Fe in coal fly ash has underpinned several studies on the use of coal fly ash as a coagulant and adsorbent. Coal fly ash coagulant was activated with H2SO4. While coal fly ash adsorbent is activated with HCl. This study aims to compare the effectiveness of the  coagulant  or  as   adsorbent,  to determine the optimum concentration of coagulant/ adsorbent addition, and to determine the effectiveness of fly ash as a coagulant/ adsorbent in reducing COD and TSS in Pulp and Paper wastewater. This research used 2 treatments, activating coal fly ash with 2M H2SO4 and 4M HCl, and then comparing the effect of fly ash coagulants and adsorbents in reducing COD and TSS wastewater. The results showed that coagulant reduced COD by 53.23% and TSS by 60.1%, more effective  than  adsorbent  which  only reduced COD by 6.38%, and increased TSS value by 7.2%. However, it has not yet below the quality standards. Numerical  analysis  using  3rd  order polynomials shows that doses of 41,000-42,000 ppm of coagulant can reduce COD below the quality standard. This concludes is coal fly ash coagulant is effective in reducing COD and TSS of pulp and paper wastewater, with the optimal dose to reduce COD below the quality standard, is 41,000 - 42,000 ppm.